Rasionalitas dan Ekonomi Islam - Munthe, Endang Suriyani; Yunanda, Mey; Ningtyas, Pratiwi Ayu; Zein, Ahmad Wahyudi (STAI Denpasar Bali, 2025)
Rationality in Islamic economics is a concept rooted in sharia principles, which aims to create a balance between material and spiritual needs. In contrast to conventional approaches to rationality which are often oriented towards maximizing utility and profit, Islamic economics expands the concept of rationality to include moral, ethical and social justice dimensions. Rationality in Islamic economics emphasizes economic decisions that not only take into account individual interests but also collective interests and sustainability.This concept involves compliance with halal and haram rules, as well as principles such as zakat, the prohibition of usury, and the importance of sharing risks in financial transactions. Islamic economics seeks to create a just and sustainable economic system, where the main goal is not only the accumulation of wealth but also social welfare and equitable distribution. Thus, rationality in Islamic economics does not only refer to economic efficiency, but also to moral and spiritual responsibility, which reflects the integration between faith and economic action.This study highlights how these principles can be applied in a modern economic context, as well as the potential of Islamic economics in providing solutions to global economic challenges, such as social injustice and unequal distribution of wealth.